Communication Tools for Geographically Distributed Work - Liukkunen, Kari; Markkula, Jouni (International Journal of Industrial Engineering and Management, 2012)
In the current globalized business environment, companies face increasing collaboration challenges at different levels of operation. Economic factors, as well as advancements in technology, have led to the globalization of design and production, which are organized into distributed projects. Information management and communication system issues are highlighted in collaboration within global companies with different branch offices and between organizations in business networks. In this paper, we tackle these communication and collaboration challenges by studying how different communication technologies can support geographically distributed work. We address this question by identifying from the literature the key categories of collaboration challenges and by conducting an empirical, multiple-case study of three companies from 2009 to 2011. The companies consisted of a small consulting company, a medium-sized software company, and a company-driven large R&D project. In this paper, we present our findings concerning the suitability of different communication tools in various working contexts. Article history: Received (22 December 2011); Revised (23 January 2012); Accepted (02 February 2012)